2021
DOI: 10.3390/toxins13040285
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Some Plant and Fungal Metabolites towards Aedes albopictus (Diptera, Culicidae)

Abstract: Aedes albopictus (Skuse) is a widespread mosquito, a vector of important human arboviruses, including Chikungunya, Dengue and Zika. It is an extremely difficult species to control even for the onset of resistances to chemicals insecticides, therefore ecofriendly products are urgently needed. In this study, the activity of Amaryllidaceae alkaloids and some of their semisynthetic derivatives, of 2-methoxy-1,4-naphthoquinone and two analogues, of cyclopaldic acid and epi-epoformin on the survival and development … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…These pieces of evidence definitely demonstrated that CA is a non-specific in vivo phytotoxin. More recently, in the search for natural products as an alternative to synthetic pesticides, CA has been reported to possess insecticidal [ 12 , 13 , 14 ], fungicidal [ 15 ] as well as herbicidal [ 16 ] activities. However, despite its remarkable biological properties, information about the effects of CA at the cellular and molecular level is still very poor.…”
Section: Introductionmentioning
confidence: 99%
“…These pieces of evidence definitely demonstrated that CA is a non-specific in vivo phytotoxin. More recently, in the search for natural products as an alternative to synthetic pesticides, CA has been reported to possess insecticidal [ 12 , 13 , 14 ], fungicidal [ 15 ] as well as herbicidal [ 16 ] activities. However, despite its remarkable biological properties, information about the effects of CA at the cellular and molecular level is still very poor.…”
Section: Introductionmentioning
confidence: 99%
“…Among these there are alkaloids isolated from Amaryllidaceae and alkylamides [7,8], with the latter being a broad and expanding group found in at least 33 plant families [8]. Alkylamides and alkaloids have been observed to have antimicrobial [9][10][11][12][13][14], antiprotozoal [11,15], antiviral [16,17], insecticidal [18][19][20][21], nematocidal [22], cytotoxic [17], anticancer [23][24][25][26][27][28][29][30][31][32], acetylcholinesterase inhibition [27,28], and bioherbicidal activities [20,30]. Some plant extracts with potential herbicidal activity were also appropriately formulated in biopolymers [31,32].…”
Section: Introductionmentioning
confidence: 99%